Pengaruh E-Marketing Terhadap Perilaku Konsumtif Remaja Pada Akun Instagram @aerostreet - Caesar Mukti Al Ghozali; Sri Wahyuning Astuti (Universitas Hamzanwadi, 2023)
The purpose of this research is to analyze how e-marketing influences the purchasing habits of adolescent Instagram users who follow the @aerostreet account. This study employs a descriptive quantitative methodology that uses questionnaires to gather primary data about a phenomena. Purposive random sampling was used to identify 100 young adult Instagram users who follow the @aerostreet account as the research sample. This study used multiple linear regression analysis and descriptive statistics to examine the data. According to the data collected and analyzed, e-marketing has a notable and beneficial effect on the purchasing habits of the adolescent audience that frequents the Instagram account @aerostreet